Challenges, strategies, and lessons learned from a participatory community intervention study to promote female condoms among rural sex workers in Southern China - Weeks, M.; Liao, S.; Li, F.; Li, Jianghong; Dunn, J.; He, B.; He, Q.; Feng, W.; Wang, Y. (Guilford Publications, Inc., 2010)
China faces a rapidly emerging HIV epidemic and nationwide resurgence of sexually transmitted infections associated with a growing sex industry. Community empowerment and capacity building through community-based participatory research partnerships show promise for developing, testing, and refining multilevel interventions suited to the local context that are effective and appropriate to address these concerns. However, such efforts are fraught with challenges, both for community collaborators and for researchers. We have built an international team of scientists from Beijing and the United States and collaborating health policy makers, health educators, and care providers from Hainan and Guangxi Province Centers for Disease Prevention and Control and the local counties and towns where we are conducting our study. This team is in the process of testing a community-wide, multilevel intervention to promote female condoms and other HIV prevention within sex-work establishments. This article presents lessons learned from our experiences in the first two study sites of this intervention trial. © 2010 The Guilford Press.